Exogenous glycogen utilization effects the transcriptome and pathogenicity of Streptococcus suis serotype 2 - Tan, Mei-Fang; Tan, Jia; Zhang, Fan-Fan; Li, Hai-Qin; Ji, Hua-Yuan; Fang, Shao-Pei; Wu, Cheng-Cheng; Rao, Yu-Ling; Zeng, Yan-Bin; Yang, Qun (Frontiers in Cellular and Infection Microbiology, 2022)
Streptococcus suis serotype 2 (SS2) is an important zoonotic pathogen that causes severe infections in humans and the swine industry. Acquisition and utilization of available carbon sources from challenging host environments is necessary for bacterial pathogens to ensure growth and proliferation. Glycogen is abundant in mammalian body and may support the growth of SS2 during infection in hosts. However, limited information is known about the mechanism between the glycogen utilization and host adaptation of SS2. Here, the pleiotropic effects of exogenous glycogen on SS2 were investigated through transcriptome sequencing. Analysis of transcriptome data showed that the main basic metabolic pathways, especially the core carbon metabolism pathways and virulence-associated factors, of SS2 responded actively to glycogen induction. Glycogen induction led to the perturbation of the glycolysis pathway and citrate cycle, but promoted the pentose phosphate pathway and carbohydrate transport systems. Extracellular glycogen utilization also promoted the mixed-acid fermentation in SS2 rather than homolactic fermentation. Subsequently, apuA, a gene encoding the unique bifunctional amylopullulanase for glycogen degradation, was deleted from the wild type and generated the mutant strain ΔapuA. The pathogenicity details of the wild type and ΔapuA cultured in glucose and glycogen were investigated and compared. Results revealed that the capsule synthesis or bacterial morphology were not affected by glycogen incubation or apuA deletion. However, extracellular glycogen utilization significantly enhanced the hemolytic activity, adhesion and invasion ability, and lethality of SS2. The deletion of apuA also impaired the pathogenicity of bacteria cultured in glucose, indicating that ApuA is indeed an important virulence factor. Our results revealed that exogenous glycogen utilization extensively influenced the expression profile of the S. suis genome. Based on the transcriptome response, exogenous glycogen utilization promoted the carbon adaption and pathogenicity of SS2.